2013
DOI: 10.1007/s00018-013-1461-7
|View full text |Cite
|
Sign up to set email alerts
|

Ligand- and cell-dependent determinants of internalization and cAMP modulation by delta opioid receptor (DOR) agonists

Abstract: Signaling bias refers to G protein-coupled receptor ligand ability to preferentially activate one type of signal over another. Bias to evoke signaling as opposed to sequestration has been proposed as a predictor of opioid ligand potential for generating tolerance. Here we measured whether delta opioid receptor agonists preferentially inhibited cyclase activity over internalization in HEK cells. Efficacy (τ) and affinity (KA) values were estimated from functional data and bias was calculated from efficiency coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 57 publications
3
56
0
Order By: Relevance
“…This construct blocks internalization by interfering with binding of endogenous barr to clathrin (Krupnick et al, 1997) and, in the conditions used in this study, it inhibits internalization induced by 15-minute exposure to SNC-80 by ∼15% (Charfi et al, 2013). The basal BRET signal in cells that were transfected with mutant barr (0.272 6 0.012) or the corresponding vector pcDNA3 (0.266 6 0.008) were not different (P 5 0.6751; n 5 6), and neither were changes induced by 15-minute exposure to forskolin (controls: 24 6 4%; mutant barr: 27 6 4%; P 5 0.6154).…”
Section: Regulation Of Camp Signaling By Dor Endocytosismentioning
confidence: 77%
See 1 more Smart Citation
“…This construct blocks internalization by interfering with binding of endogenous barr to clathrin (Krupnick et al, 1997) and, in the conditions used in this study, it inhibits internalization induced by 15-minute exposure to SNC-80 by ∼15% (Charfi et al, 2013). The basal BRET signal in cells that were transfected with mutant barr (0.272 6 0.012) or the corresponding vector pcDNA3 (0.266 6 0.008) were not different (P 5 0.6751; n 5 6), and neither were changes induced by 15-minute exposure to forskolin (controls: 24 6 4%; mutant barr: 27 6 4%; P 5 0.6154).…”
Section: Regulation Of Camp Signaling By Dor Endocytosismentioning
confidence: 77%
“…On the other hand, ligand signaling ability and endocytosis promoted over the time course of the experiment were predictive of the rate of decline in of the initial cAMP response. We previously showed that DOR ligands display different internalization profiles in HEK cells and neurons (Charfi et al, 2013). It would therefore be of interest to corroborate whether the time course of cAMP responses follow the distinct internalization profiles displayed by different ligands in HEK cells and neurons.…”
Section: Tablementioning
confidence: 89%
“…The structurally related dipeptide analog Dmt-Tic-NH-CH(CH 2 COOH)-Bid (UPF-512; Bid is 1H-benzimidazole-2-yl) is also a potent DOPr agonist (Balboni et al, 2002b). This compound displayed partial efficacy to inhibit cAMP production in human embryonic kidney (HEK) cells and to induce internalization in rat cortical neurons (Charfi et al, 2014) with anxiolytic-and antidepressant-like activities when administered peripherally to mice (Vergura et al, 2008). (Fig.…”
Section: D-opioid Receptor Ligandsmentioning
confidence: 99%
“…Several studies have shown that different ligands differ considerably in their ability to recruit barr to DOPr (Keith et al, 1996;Molinari et al, 2010;Audet et al, 2012;Charfi et al, 2014). The factors contributing to these differences are multiple.…”
Section: B D-opioid Receptor-b-arrestin Interactionmentioning
confidence: 99%
See 1 more Smart Citation